Arriving late and lean at a stopover site is selected against in a declining migratory bird population - Peng, He‐Bo; Ma, Zhijun; Rakhimberdiev, Eldar; van Gils, Jan A.; Battley, Phil F.; Rogers, Danny I.; Choi, Chi‐Yeung; Wu, Wei; Feng, Xuesong; Ma, Qiang; Hua, Ning; Minton, Clive; et al. (The Journal of animal ecology, 2023)
Loss and/or deterioration of refuelling habitats have caused population declines in many migratory bird species but whether this results from unequal mortality among individuals varying in migration traits remains to be shown. Based on 13 years of body mass and size data of great knots ( Calidris tenuirostris ) at a stopover site of the Yellow Sea, combined with resightings of individuals marked at this stopover site along the East Asian‐Australasian Flyway, we assessed year to year changes in annual apparent survival rates, and how apparent survival differed between migration phenotypes (i.e. migration timing and fuel stores). The measurements occurred over a period of habitat loss and/or deterioration in this flyway. We found that the annual apparent survival rates of great knots rapidly declined from 2006 to 2018, late‐arriving individuals with small fuel stores exhibiting the lowest apparent survival rate. There was an advancement in mean arrival date and an increase in the mean fuel load of stopping birds over the study period. Our results suggest that late‐arriving individuals with small fuel loads were selected against. Thus, habitat loss and/or deterioration at staging sites may cause changes in the composition of migratory phenotypes at the population‐level. 迁徙停歇地丧失和/或退化导致许多候鸟的种群数量下降，但这是否是由于不同迁徙表型个体的死亡率差异所造成的，仍有待证明。 根据黄海区域的一个迁徙停歇地大滨鹬( Calidris tenuirostris )13年环志所记录的体重和体型大数据，并结合在东亚‐澳大利西亚迁飞区对标记个体的观察记录，我们评估了大滨鹬存活率的年际变化，以及不同迁徙表型(迁徙时间和能量储备)的存活率差异。本研究是在迁飞区发生栖息地丧失和/或退化期间进行的。 我们发现，从2006年到2018年，大滨鹬的年存活率迅速下降，迁徙日程较晚且能量储备较少的个体的存活率最低。在研究期间，大滨鹬到达该迁徙停歇地的日期有所提前，能量储备也有所增加。 研究结果表明，迁徙日程较晚且能量储备较少的个体被选择性地淘汰。因此，迁徙停歇地丧失和/或退化可能会导致迁徙表型的组成在种群水平上发生变化。